An unexpected diversity of trypanosomatids in fecal samples of great apes - Votýpka, Jan; Pafčo, Barbora; Modrý, David; Mbohli, Donald; Tagg, Nikki; Petrželková, Klára J (International journal for parasitology. Parasites and wildlife, 2018)
Charismatic great apes have been used widely and effectively as flagship species in conservation campaigns for decades. These iconic representatives of their ecosystems could also play a role as reservoirs of several zoonotic diseases. Recently it was demonstrated that African great apes can host Leishmania parasites (Kinetoplastea: Trypanosomatidae). Given that this finding raised a strong negative reaction from leishmania experts and the subsequent discussion did not lead to a clear resolution, we decided to analyze wild gorilla (Gorilla gorilla gorilla) and chimpanzee (Pan troglodytes troglodytes) fecal samples collected from the same area in Cameroon as in the original study. Fecal samples, used to circumvent the difficulties and ethics involved in obtaining blood samples from endangered wild apes, were screened by three different PCR assays for detection of Leishmania DNA. We did not detect any leishmania parasites in analyzed feces; however, sequencing of SSU rRNA revealed an unexpected diversity of free-living bodonids (Kinetoplastea: Bodonidae) and parasitic trypanosomatids (Kinetoplastea: Trypanosomatidae) other than Leishmania. A single detected Phytomonas species, found in chimpanzee feces, most likely originated from animal plant food. On the other hand, the presence of four free-living bodonid species and four parasitic insect monoxenous trypanosomatid, including two possible new species of the genus Herpetomonas, could be explained as ex post contamination of feces either from the environment or from flies (Diptera: Brachycera).
Keywords: Feces; Gorilla; Trypanosomatids; Herpetomonas; Leishmania; PCR; Detection; Chimpanzee